ANALISIS KESALAHAN I’ROB DALAM MEMBACA TEKS BAHASA ARAB KITAB ILMU TAFSIR SISWI KELAS V MAK MA’HAD TAHFIDZ AL-QUR’AN AL-AMIEN PRENDUAN - Ainul Yakin; Farihatul Hasanah (Institut Dirosat Islamiyah Al-Amien Prenduan, 2020)
The main key in reading the book of turots (Arabic text) properly and correctly is to master the rules of nahwu and shorrof science because of the knowledge of nahwu and shorrof. In reading books in Arabic, it must be done properly and correctly in accordance with the applicable rules, namely in accordance with the rules of nahwu and shorrof. If one has understood the science of nahwu and shorrof then there will be no error of dignity, position, and meaning, and if one is wrong in reading a book in Arabic then, the result will cause an error in its meaning or meaning to change and will give rise to a different interpretation, even if the error is few. The focus of this research is to find out how I'rob's error in reading Arabic texts in the book of Tafsir students of class V MAK B Ma'had Tahfidz Al-Qur'an Al-Amien Prenduan and to find out the factors that cause the error. This research is qualitative research with a descriptive type of research. The theory used is Ellis's theory: collecting errors, identifying mistakes, explaining errors, classifying errors, evaluating errors, and using observation, interview and documentation methods. The results obtained in this study are 1). The forms of I'rob errors When reading the book of interpretation in class V MAK B Ma'had Tahfidz Al-Qur'an Al-Amien Prenduan are: a). I'rob mubtada' Khobar, b). Idhofah, c). Athof, d). Amil Nawasikh, e). Jar letters, f). Fail, and g). Na'at. 2). Factors that cause students to read the wrong book of interpretation are internal factors and external factors. Internal factors include a). Lack of understanding of Nahwu and Shorrof science rules, b). lack of silverware in reading the book, c). Fear of being wrong or not confident in reading the book, d). No focus, e). Don't know Muphrodat, and f). Lack of interest. External factors include: a). A less conducive classroom atmosphere, and b). lack of time.